Impact of Age on Short- and Long-Term Outcomes after Pancreatoduodenectomy for Periampullary Neoplasms. (16th April 2020) - Gruppo, Mario; Tolin, Francesca; Franzato, Boris; Pilati, Pierluigi; Spolverato, Ylenia Camilla; Zingales, Francesca; Angriman, Imerio; Bardini, Romeo
Abstract : Background . Although mortality and morbidity of pancreatoduodenectomy (PD) have improved significantly over the past years, the impact of age for patients undergoing PD is still debated. This study is aimed at analyzing short- and long-term outcomes of PD in elderly patients. Methods . 124 consecutive patients who have undergone PD for pancreas neoplasms in our center between 2012 and 2017 were analyzed. Patients were divided into two groups: group I (<75 years) and group II (≥75 years). Demographic features and intraoperative and clinical-pathological data were collected. Primary endpoints were perioperative morbidity and mortality; complications were classified according to the Clavien-Dindo Score. Secondary endpoints included feasibility of adjuvant treatment and overall survival rates. Results . A total of 106 patients were included in this study. There were 73 (68.9%) patients in group I and 33 (31.1%) in group II. Perioperative deceases were 4 (3.6%), and postoperative pancreatic fistulas were 34 (32.1%). Significant difference between two groups was demonstrated for the ASA Score (p = 0.004 ), Karnofsky Score (p = 0.025 ), preoperative jaundice (p = 0.004 ), and pulmonary complications (p = 0.034 ). No significance was shown for diabetes, radicality of resection, stage of disease, operative time, length of stay, postoperative complications according to the Clavien-Dindo Score, postoperative mortality, pancreatic fistula, and reoperation rates. 69.9% of the patients in group I underwent adjuvant treatment vs. 39.4% of the older ones (p = 0.012 ). Mean overall survival was 28.5 months in group I vs. 22 months in group II (p = 0.909 ). Conclusion . PD can be performed safely in elderly patients. Advanced age should not be an absolute contraindication for PD, even if greater frailty should be considered. The outcome of elderly patients who have undergone PD is similar to that of younger patients, even though adjuvant treatment administration is significantly lower, demonstrating that surgery remains the main therapeutic option.